DESIGN POINT OF SALE (POS) PADA APOTIK CENTURY HEALTH CARE BEKASI BERBASIS WEB DENGAN PENDEKATAN TEORY WATERFALL - Khotimah, Siti; Sinnun, Ahmad (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2021)
The rapid development of information technology helps us in helping human activities become more dynamic, in the current state of the covid-19 pandemic which requires people to keep their distance and increase their activities at home. Pharmacies as providers of medicines play an important role in providing the needs of drugs and personal protective equipment for today's society, the author's observations find deficiencies that can be maximized from the transaction system at pharmacies, in terms of buyers having to travel to the location to buy medicine and health needs. On the pharmacy side, we need a way for online sales and product introduction, in this case the author designs a website-based drug sales information system for time and energy efficiency with the aim of making it easier for buyers and reducing the level of meetings between buyers and sellers. Through the point of sales website, the author hopes to increase sales and convenience for customers as well as the accuracy of sales data.